Interesting case of an abdominal wall Merkel cell carcinoma highlighting the importance of developing an Australian clinical practice guideline. Issue 9 (13th September 2020) - Nassour, Anthony-Joe; Ashrafi, Darius; Lah, Kevin; Sivananthan, Suntharalingham
Abstract : A 66-year-old Australian male farmer was referred for management of an asymptomatic, rapidly expanding, anterior abdominal wall mass. It was firm and well circumscribed. There were no overlying skin changes, constitutional symptoms or weight loss. His medical history included small bowel obstruction and resection from a Meckel's diverticulitis and a 40-pack-year smoking history. Core biopsy was suggestive of a neuroendocrine tumour and Gallium-68-Dodecane-Tetraacetic-Acid (68GaTate) positron emission tomography revealed an avid solitary lesion confined to the subcutaneous space in the left anterior abdominal wall. Wide local excision was performed, and histopathology revealed Merkel cell carcinoma (MCC). Although classically regarded as a primary cutaneous neuroendocrine tumour, MCC may originate from the subcutaneous fat without obvious skin involvement. Older patients with asymptomatic, rapidly enlarging lesions, particularly if immunosuppressed, with significant ultraviolet sunlight exposure, should raise a high index of suspicion for MCC. Like melanoma, non-metastatic MCC should be treated aggressively for best prognosis.